Tandem mass tag-based quantitative proteomic analysis of effects of multiple sevoflurane exposures on the cerebral cortex of neonatal and adult mice - Feng, Jingyu; Lin, Hua; Zhao, Yue; Yang, Yongyan; Zhuang, Xiaoli; Yu, Yang; Yu, Yonghao (Frontiers in Neurology, 2022)
Sevoflurane is the most commonly used general anesthetic in pediatric surgery, with a known potential to induce neurotoxicity. Long-term or multiple sevoflurane exposures were shown to cause cognitive deficits in newborn but not adult mice, whereas short-term or single inhalation minimally impacted cognitive function at both ages. However, the mechanism underlying these effects remains unclear. Herein, 6- and 60-day-old C57BL/6J mice in the sevoflurane group were administered 3% sevoflurane plus 60% oxygen for three consecutive days, for a duration of 2 h; mice in the control group only received 60% oxygen. Cortex tissues were harvested on days 8 or 62. Tandem mass tag (TMT)pro-based quantitative proteomics combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis, Golgi staining, and western blotting analysis were performed to analyze the impact of multiple sevoflurane anesthesia on the cerebral cortex of mice in distinct age groups. Mice were subjected o the Morris water maze test from postnatal day (P)30 to P36 or P84 to P90 after control or multiple sevoflurane treatments. Sevoflurane anesthesia affected spatial learning and memory and diminished dendritic spines, primarily in newborn mice, with no significant alteration observed in mature animals. Overall, 6247 proteins were measured using the combined quantitative proteomics methods of TMTpro-labeled and LC-MS/MS; among these, 443 were associated with the age-dependent neurotoxic mechanism induced by repeated sevoflurane anesthesia. Based on western blotting analysis, elevated chromogranin B (CHGB), phosphatase and tensin homologue (PTEN), and microtubule-associated protein 2c (MAP2c) protein expression or reduced superoxide dismutase 2 (SOD2) protein expression might mediate sevoflurane-induced brain damage in newborn mice. Our findings will help further elucidate the mechanism underlying age-dependent anesthetic neurotoxicity and contribute to identifying effective protective strategies in the developing brain subjected to general anesthesia.